2019
DOI: 10.1021/acsenergylett.9b00459
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Lithium Metal in Poly(ethylene oxide)

Abstract: We demonstrate that lithium metal is sparingly soluble in poly(ethylene oxide) (PEO). 7 Li NMR shows that when a PEO sample is placed in contact with lithium metal at elevated temperatures, a lithium species dissolves and diffuses into the bulk polymer. A lithium/PEO/lithium electrochemical cell, containing no lithium salts, shows increasing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…[34,35] Moreover, widely researched solid polymer electrolytes (SPEs) like PEO cannot stand the intensive chemical reactivity of lithium metal. [36] Lithium nuclear magnetic resonance ( 7 Li NMR) shows that lithium species can dissolve and diffuse into the bulk polymer, when a pure PEO sample is placed in contact with lithium metal at elevated temperatures. More examples are summarized in Table 1.…”
Section: Poor Chemical or Electrochemical Compatibilitymentioning
confidence: 99%
“…[34,35] Moreover, widely researched solid polymer electrolytes (SPEs) like PEO cannot stand the intensive chemical reactivity of lithium metal. [36] Lithium nuclear magnetic resonance ( 7 Li NMR) shows that lithium species can dissolve and diffuse into the bulk polymer, when a pure PEO sample is placed in contact with lithium metal at elevated temperatures. More examples are summarized in Table 1.…”
Section: Poor Chemical or Electrochemical Compatibilitymentioning
confidence: 99%
“…Interestingly, the conductivity increase seems to proceed in three stages: in the first 5 h conductivity is unchanged, followed by a rapid increase from 6 to 9 h, and finally a slower increase after 9 h. Such increment profile was also observed in Galluzzo et al's work. [19] One hypothesis to explain the multistage reaction profile is proposed as follows: in the beginning of the PEO/Li contact, the reaction only initiates at some well-contacted spots. Limited amounts of Li þ ions are generated at the interface, which are too far away from the electrodes to make the whole film conductive.…”
Section: Resultsmentioning
confidence: 99%
“…Galluzzo et al reported conductivity increases in a salt-free, PEO-based Li|Li symmetric cells after holding at 120 C for 10 days. [19] They proposed that Li metal can be dissolved by PEO in the form of Li þ ions and free electrons. This is partially supported by 1) Fourier transform infrared spectroscopy (FTIR) data of PEO showing that the PEO backbone remains intact in the bulk of the polymer and 2) electrochemical experiments showing there is no Li þ concentration gradient in the electrolyte, though it is unlikely that the postulated "free" electrons remain unreacted.…”
mentioning
confidence: 99%
“…The mapping results for these isles in a battery cycled with no external pressure shows that the formation of isles depends on the reactions that take place in these regions and not on the applied pressure on the battery, as suggested by Hovington et al 1 . Galluzzo et al 26 has shown that lithium metal dissolves and diffuses in the polyether bulk as Li + and a free electron. Lithium metal may then reduce the salt in the polymer.…”
Section: Resultsmentioning
confidence: 99%